Changes in duration and intensity of the world`s top-level badminton matches: A consideration of the increased acute injuries among elite women`s singles players - Iizuka, T.; Hirano, K.; Atomi, T.; Shimizu, M.; Atomi, Y. (Sports, 2020)
The purpose of this study was to clarify whether there have been any specific changes in the characteristics of the world`s top-level women`s singles badminton matches compared to men`s singles matches after the current badminton scoring system was implemented in 2006. We compared the characteristics of the matches between the Super Series tournaments in 2007 and 2017. Match duration increased as the rally and rest times increased in both men`s and women`s singles matches. Specifically, in women`s singles, it was suggested that a further increase in physical demands because of the increased number of shots per second may have resulted in longer rest time in proportion to rally time. Moreover, increases in match duration (final eight, 53.3 6.6 min; early rounds, 42.1 3.6 min; P < 0.05) and number of shots per rally (final eight, 10.4 1.2; early rounds, 8.7 1.1; P < 0.05) in women`s singles were more prominent in the final eight rounds (quarterfinals, semifinals, and finals) than in the early rounds (rounds 1 and 2). The recent changes in characteristics of the world`s top-level badminton matches may account for the increased acute injuries that are frequently observed in elite women`s singles players. Thus, appropriate training programs are crucial to e ectively improve performance and prevent injuries among elite badminton players.